Developing a water treatment system for Subsea Gas processing plant - Honer Badi M Nazhat, Dana (Curtin University, 2006)
The petroleum industry is currently moving to meet the ever-rising demand for oil and gas production. As onshore fields become depleted and decline in production, exploration and production companies have started venturing further offshore. To support this activity, there is need for new subsea production technologies to develop deepwater and ultra deepwater fields.Woodside Hydrocarbon Research Facility (WHRF) at Curtin University of Technology is working on natural gas dehydration processing using gas hydrate technology. Through the studies, a novel gas dehydration process has been developed and now proposed for subsea application. Natural gas dehydration processes generate both a treated dry gas stream and a waste stream of condensate consisting of both hydrocarbons and water. This condensate can be reinjected to the reservoir formation but this is not always economic or practical. Availability of an alternative means of treatment and disposal of the condensate would be advantageous. This study aims to investigate and to provide a basis for the design of such an alternative scheme by constructing a floating separator for the treatment and disposal of waste condensate from subsea dehydration stage.A model was developed to simulate the process of evaporation of condensate from the proposed floating separator. The calculations were performed taken into account zero wind speed and an ambient temperature around 34 C. The simulation results showed that condensate skimming time was found to be 15 days for flowrate (Qin) of 100 bbd associated with specific separator diameter and total height dimensions. By considering the ratio of diameter to total height of 2.5, the floating separator was designed to enhance the evaporation rate and to get overall structure stability due to the mechanical restrictions that might be encountered in the sea.